Penggunaan Unsur Serapan pada Teks Laporan Hasil Observasi Siswa Kelas X SMAN 5 Depok dan Implikasinya terhadap Pembelajaran Bahasa Indonesia - Muhammad Rizky Alfiansyah; Friza Youlinda Parwis (Journal on Education, 2022)
The purpose of this study was to determine the use of absorption elements in the report text of the observations of class X students of SMAN 5 Depok. In compiling the work steps, the research method used to analyze this text uses a descriptive method that aims to describe objectively the use of absorption elements contained in the text of the observation report. After analyzed the report text of class X students of SMAN 5 Depok, there were absorption elements with the process of adoption absorption, phonological adaptation, orthographic adaptation, phonological and orthographic adaptation, and morphological adaptation.